2018
DOI: 10.1038/s41467-018-05746-9
|View full text |Cite
|
Sign up to set email alerts
|

Deficient humoral responses and disrupted B-cell immunity are associated with fatal SFTSV infection

Abstract: Severe Fever with Thrombocytopenia Syndrome (SFTS), an emerging infectious disease caused by a novel phlebovirus, is associated with high fatality. Therapeutic interventions are lacking and disease pathogenesis is yet to be fully elucidated. The anti-viral immune response has been reported, but humoral involvement in viral pathogenesis is poorly understood. Here we show defective serological responses to SFTSV is associated with disease fatality and a combination of B-cell and T-cell impairment contribute to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(125 citation statements)
references
References 69 publications
9
115
1
Order By: Relevance
“…However, the low number of clinical cases of infection with certain SFTSV genotypes, especially of the reassortant genotypes, impedes the determination of the association between genotype and case mortality. Further, recently, Song et al demonstrated that fatality induced by SFTSV infection is associated with the absence of specific IgGs to viral nucleocapsid and glycoprotein due to a failure in B cell class switching (37). Similarly, in our preliminary ELISA study with ferret sera, we found that SFTSV-infected healthy young ferrets exhibited a strong IgG response, while aged ferrets showed very limited IgG responses against the NP of the B-1/2014 SFTSV strain (unpublished observations).…”
Section: Discussionsupporting
confidence: 80%
“…However, the low number of clinical cases of infection with certain SFTSV genotypes, especially of the reassortant genotypes, impedes the determination of the association between genotype and case mortality. Further, recently, Song et al demonstrated that fatality induced by SFTSV infection is associated with the absence of specific IgGs to viral nucleocapsid and glycoprotein due to a failure in B cell class switching (37). Similarly, in our preliminary ELISA study with ferret sera, we found that SFTSV-infected healthy young ferrets exhibited a strong IgG response, while aged ferrets showed very limited IgG responses against the NP of the B-1/2014 SFTSV strain (unpublished observations).…”
Section: Discussionsupporting
confidence: 80%
“…**P = 0.0045, ****P < 0.0001. (27). Normal plasmablasts are activated B cells in the germinal center that have undergone somatic hypermutation and class-switching recombination (38).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the high awareness within the medical community in SFTS-endemic areas, and the use of antiviral therapy such as ribavirin, the case fatality rate of SFTS is still as high as 15%, which is the same as other severe viral diseases including viral hemorrhagic fevers (15). In SFTS, inflammatory cytokine storms (11,(16)(17)(18)(19) as well as impairment of immune responses including innate immunity (14,(20)(21)(22)(23)(24)(25), antiviral T cell function (26), and antiviral humoral responses (27) have important roles in the pathogenic progress of lethal infections. Immune impairment and high viral loads are also characteristics of several other viral hemorrhagic fevers (28), but these diseases differ in terms of pathology and pathogenesis, about which little is known for SFTS.…”
Section: Introductionmentioning
confidence: 99%
“…As a systemic virus infectious disease with overall dysfunction of cellular and humoral immunity [11,12], SFTS patients were susceptible to bacterial and fungal infection. Procalcitonin (PCT) is a useful parameter to guide antibiotic therapy in severe sepsis patients [13].…”
Section: Discussionmentioning
confidence: 99%